EDUCAÇÃO AMBIENTAL E A FORMAÇÃO DO PEDAGOGO - CRUZ, IANDRA APARECIDA DA (2022)
Environmental Education, as a field of Knowledge, proves to be essential in discussions that advocate current socio-environmental conflicts, several surveys show that Environmental Education in educational spaces is worked in a conservative and naïve way, this fact may be related to initial training and of teachers, mainly those of Basic Education. The National Curriculum Guidelines For Environmental Education recommend that Environmental Education should be worked on at different levels and teaching modalities. The research entitled Environmental Education and the formation of pedagogue, sought to analyze the knowledge of the students of the course of a higher education institution, on the environmental theme acquired in the course. It is a reserch, with a qualitative basis, a total of 46 academics participated in our reserch, data werw collected through a questionnaire and focus group. The survey results revealed that even though academics have had access to the foundations and methodologies of a critical Environmental Education, what predominates is the conservative and pragmatic aspect in their responses. This result can be attributed to the difficulties and influences faced by these academics throughout their training, from initial training to even during the undergraduate course, such as a conservative basic education, or wide dissemination of pragmatic Environmental Education, through the media communication.